Frequency of skeletal metastasis on 18F-fluorodeoxyglucose positron emission tomography/computed tomography with negative computed tomography at Institute of Nuclear Medicine and Oncology - Mariam Fayyaz; Muhammad Numair Younis; Sheikh Danial Hanan; Syed Zain Ul Abidin; Rimsha Badar; Muhammad Waseem Akram (Asian Journal of Medical Sciences, 2022)
Background: Skeletal metastasis (SM) with skeletal related events (SREs) occurs in up to 70% of breast cancer and more than 50% of malignant tumors. Whole-body 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) used to characterize the metabolic, anatomic, and morphologic status of suspected bone lesions. SMs are detected using multiple modalities; however, FDG PET/CT may offer a single investigation to detect SM combining the strength of functional imaging and radiological imaging simultaneously.